Relationship between Psychological Adjustment and Life Satisfaction among Caregivers of Children with Intellectual Disabilities - Habib Abd Ali Al-Hasnawi, Karrar; Hussein Al Dujaili, Arafat (International Journal of Psychosocial Rehabilitation, 2020)
Intellectual disabilities (IDs) are permanent disabilities that appear during the developmental years and are characterized by limitations in adaptive behaviors and below-average general intellectual functions (intelligence quotient (IQ) below 70). They are very common among children around the world, and the rates of greater children surviving are likely to increase through improved medical care. Besides, intellectual disabilities are considered the most common serious developmental disabilities. The birth of a disabled child creates a significant impact on the parents, as shown by many studies, most of which focused on the psychological adjustment of the parents. The importance of this issue lies in the adjustment difficulties that exist for parents having a disabled child. Effective parenting is essential to the intellectual, physical, social, and emotional development of a child. The psychological adjustment of the parents of children with IDs has a significant impact on the child's development regardless of the child’s intellectual functioning. Aim of the study: This study aims to assess the levels of psychological adjustment and life satisfaction among caregivers of children with intellectual disabilities and determine the relationship between psychological adjustment and life satisfaction among caregivers of children with intellectual disabilities. Research design: A study and descriptive (correlation) quantitative design were utilized in order to achieve the objectives of this study. from the period of 15th October 2019 to 9th September 2020. Study setting: The study was conducted at AL-Najaf city, AL-Raja Institute, and Dema Institute for special needs children. Study sample: A nonprobability sampling technique (purposive sampling) of 112 children with IDs and 112 caregivers is included in the study. All children are medically diagnosed with IDs. Tools: The questionnaire was adopted and developed by the researcher to achieve the objectives of the study, which consists of four parts: part (1) consist of children's socio-demographic data and children's clinical data, part (2) caregiver's socio-demographic data, part (3) Brief Cope Inventory scale, and part (4) Satisfaction with Life Scale (SWLS). the validity of the study instrument achieved through a panel of experts. The data were described statistically and analyzed through the use of descriptive and inferential statistical analysis procedures. Results: The results of the present study indicated that the overall assessment for caregivers' psychological adjustment was poor; the overall assessment of caregivers' life satisfaction was unsatisfied with their life, and there is a highly significant relationship between psychological adjustment and life satisfaction among caregivers of children with intellectual disabilities. Conclusions: The study concluded that the male is the dominant gender for the children with intellectual disabilities, intellectual disabilities are most commonly occurs among the first child in the family, the mild disability is the most common level or degree of children with intellectual disabilities, females (mothers) are the dominant caregivers for the children with intellectual disabilities, the psychological adjustment among caregivers of children with intellectual disabilities is poor, the majority of the caregivers of children with intellectual disabilities are unsatisfied about their life due to their children's disability, and there is a significant and positive relationship between psychological adjustment and  life satisfaction among caregivers of children with intellectual disabilities. Recommendations: The current study recommends encouraging the faculty staff and postgraduate students to benefit from the results of the present study, and another study should be conducted about how to improve the psychological adjustment among caregivers of children with intellectual disabilities, and another study should be conducted about how to increase the caregivers' life satisfaction.